The Influence of Flash Sales, Viral Marketing and Electronic Word of Mouth (E-WOM) on the Purchase Intention of Z Generation in Online Shopping on Tiktok Shop Marketplace - Faturrohman, M.Deisry; Widarta (PT FORMOSA CENDEKIA GLOBAL, 2024)
The primary goal of this study is to determine the impact of Flash Sales, Viral Marketing, and Electronic Word of Mouth (E-WOM) on Purchase Intention in the TikTok Shop Marketplace. The research sample consisted of 100 respondents determined using purposive sampling. Multiple linear regression was the analytical tool utilized. According to the research findings, Flash Sales have little effect, however Viral Marketing and Electronic Word of Mouth (E-WOM) have a favorable and significant effect on Purchase Intention. The results and discussion of the study that the Flash Sale variable does not significantly affect purchase intention. This indicates that Flash Sale is not a primary factor influencing Purchase Intention.